2006
DOI: 10.1159/000092923
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Dementia

Abstract: The association between stroke and dementia is frequent. The prevalence of poststroke dementia (PSD) ranges from 6 to 32%, depending on the population studied, the criteria used for the diagnosis of dementia, and the time interval between the stroke and the neuropsychological assessment. The risk of PSD is high immediately after stroke and remains higher than in controls in stroke patients nondemented 3 months after stroke. Not all cases of PSD are vascular in origin, with about one third of demented patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
21

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 138 publications
(287 reference statements)
4
51
0
21
Order By: Relevance
“…First, demographics and clinical characteristics of patients which showed increasing age associated with an increased risk of poststroke dementia in most studies. 16,[18][19][20][21]23,25,32 Adding demographics factors showed that the risk of incident dementia elevated in relation to older age especially > 80 years (RR 4.66, 95%CI; 2.36 to 9.22) and age 70 to 79 years (RR 2.68, 95%CI; 1.52 to 4.74) versus age 60 to 69 years. 28 33 Previous mental decline was the correlation of dementia in logistic regression analysis (OR 1.20, 95%CI; 1.10 to 1.40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, demographics and clinical characteristics of patients which showed increasing age associated with an increased risk of poststroke dementia in most studies. 16,[18][19][20][21]23,25,32 Adding demographics factors showed that the risk of incident dementia elevated in relation to older age especially > 80 years (RR 4.66, 95%CI; 2.36 to 9.22) and age 70 to 79 years (RR 2.68, 95%CI; 1.52 to 4.74) versus age 60 to 69 years. 28 33 Previous mental decline was the correlation of dementia in logistic regression analysis (OR 1.20, 95%CI; 1.10 to 1.40).…”
Section: Resultsmentioning
confidence: 99%
“…26 Third, stroke factors such as the previous stroke has been indicated as a risk factor for poststroke dementia. 11,18,22 A study on frequency and predictors of dementia after ischemic stroke showed that prior stroke was independent predictors of dementia (OR 2.53, 95%CI; 1.42 to 4.51). 26 Recurrence stroke risk factors were significantly associated with post-stroke dementia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В целом, по данным эпидемиологических исследований, распространенность КН после инсульта составляет от 22% до 96%, такой большой разброс объяс-няется неоднородностью популяции пациентов, выбором разных методик нейропсихологического обследования, включением в анализ доинсультных КН или их игнориро-ванием, выбором критериев исключения (афазия, первый или повторный инсульт и т.п.) [11,16,17]. К настоящему времени разработан специальный опросник, позволяю-щий сделать ретроспективное предположение о наличии доинсультного когнитивного снижения на основании бесе-ды с родственниками пациента («опросник родственника о когнитивном снижении у пожилого человека» -Informant Questionnaire on Cognitive Decline in Elderly -IQCODE) [18].…”
Section: частота и факторы риска когнитивных нарушений при инсультеunclassified
“…There is little evidence to suggest that executive function interventions have the potential to improve aspects of executive functioning in adults with stroke (Poulin, Korner-Bitensky, & Dawson, 2013). Evaluating the efficacy of different cognitive rehabilitation methods and approaches is very difficult due to differences in patients' ages, brain injuries, and cognitive dysfunctions, as well as the difficulties of conducting randomized clinical trials in this field (Hénon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%